Answer:
Below in bold.
Step-by-step explanation:
A. We can calculate the slope using (y2 - y1) / (x2 - x1)
= (3 - (-2)) / (1 - 6)
= 5/-5
= -1.
So the given slope of 3 or one of the points is NOT correct.
B. If the point (1, 3 ) and the slope are correct then the equation for the line (using the point-slope form) is y - 3 = 3(x - 1)
C Another point on this line would be , when x = 0 , y = 3*-1 + 3 = 0
so it's (0, 0)
D. If the given points are correct the slope is ( as above) = -1.
E. The equation for this line is
y - 3 = -1(x - 1)
y = -x + 1 + 3
y = 4 - x.